Conceptual breakthroughs in evolutionary genetics a brief history of shifting paradigms - Avise, John C. (Amsterdam Elsevier, Academic Press, 2014)
Conceptual Breakthroughs in Evolutionary Genetics is a pithy, lively book occupying a special niche--the conceptual history of evolutionary genetics--not inhabited by any other available treatment. Written by a world-leading authority in evolutionary genetics, this work encapsulates and ranks 70 of the most significant paradigm shifts in evolutionary biology and genetics during the century-and-a-half since Darwin and Mendel. The science of evolutionary genetics is central to all of biology, but many students and other practitioners have little knowledge of its historical roots and conceptual developments. This book fills that knowledge gap.
Part I. The first 50 years (1859-1910) : laying the foundations -- Part II. The next 50 years (1910-1960) : expanding the foundations -- Part III. The 1960s and 1970s : dawn of the molecular era -- Part IV. Post-1980 : elaborating and revisiting the foundations.
Includes bibliographical references and index.
Keywords: Evolutionary genetics; Electronic books